A study to assess the various factors and treatment modalities of pressure sore in a tertiary care hospital - H. S., Ravi; Mehta, Milind A. (International Surgery Journal, 2019)
Background: Pressure sores can cause physical, social and psychological suffering. The distress is caused by local factors such as pain, wound exudates and malodour (which may lead to social isolation), delayed rehabilitation (which may result in economic hardship), and serious complications such as cellulitis, osteomyelitis, septicemia, limb amputation and death. The objective of the study was to assess the various factors affecting the outcome of pressure sore and various treatment modalities in the management of pressure sore. Methods: A hospital based prospective study was carried out from August 2007 to January 2010 at V S Medical College, Ahmedabad, Gujarat. All the cases admitted with pressure sores in the hospital across all the departments were included in the study. A total of 50 cases of pressure sores which met our inclusion criteria were included in the study. Results: 50 patients of pressure sore were studied out of which, 28 (56%) patients are non-paraplegics and 22 (44%) patients are paraplegic. The most common site is sacral region 45 (60.8%), followed by ischial region 12 (16.2%) and Trochanteric region 10 (13.5%). 47 (94%) patients were treated with systemic antibiotics and 6 (12%) patients were treated with muscle relaxants for spasticity. Conclusions: Non ambulatory paraplegic patients with deep pressure sores needs surgical intervention to cover the pressure sore; while non-paraplegic patients with superficial pressure sores can be treated successfully by conservative line of management and deep pressure sores needs to be operated.